The everyday life of the «Krims» Romani ethnic group (based on the results of participant observation research) - Shevchenko, A. (ХНУ імені В.Н. Каразіна, 2012)
This article is devoted to the study of the “Krims” Gypsy subethnic group. Krims' cultural features, routine practices and patterns of behavior of its representatives are analyzed.
Статья посвящена изучению социокультурных особенностей цыганского субэтноса «Крымы». Произведен анализ повседневных практик и моделей поведения его представителей.
Keywords: Krim; routine practices; sociocultural features; Gypsy subethnic group